(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
As a result of complex clinical and endoscopic studies, 78 (32.2%) women turned out to be practically healthy. In 164 (67.8%) women, certain diseases were detected, including: and exocervicitis in 44 (27%), endometriosis of the cervix in 9 (5.5%), pseudo-erosion and erosion of the cervix 35 (21.3%) , cervical polyp in 6 (3.7%), simple and partially overlapped ectopia in 20 (12.2%), old ruptures and scars of the cervix in 8 (4.9%), narrowing and infection of the cervix in 5 ( 3%), cervical papilloma in 4 (2.4%), cervicitis caused by herpetic and fungal infection in 29 (17.7%), leukoplakia in 4 (2.4%) women. Given the clinical and echographic prognosis, women who had significant discrepancies in the diagnosis were assigned to the group of active observation by an oncogynecologist.